Implementasi Revolusi Industri 4.0 dalam Industri Mesin: Tantangan dan Peran Administrasi Negara dalam Regulasi - Fider Lumban Batu (Majalah Ilmiah METHODA, 2024)
The Industrial Revolution 4.0 has brought significant changes to the machinery industry through automation, Internet of Things (IoT), artificial intelligence (AI), and other technologies. The implementation of these technologies provides opportunities and challenges for the machinery industry, including production efficiency, quality improvement, and regulatory and policy challenges. This study aims to analyze the challenges faced by the machinery industry in implementing the Industrial Revolution 4.0 and the role of state administration in regulating and supporting this transformation. With a qualitative approach based on literature studies, this study found that adaptive regulations, incentives for industry, and increasing human resource capacity are the keys to success in implementing the Industrial Revolution 4.0. The implementation of the Industrial Revolution 4.0 in the machinery industry offers great opportunities, but also faces significant challenges such as infrastructure readiness, limited skilled labor, and regulations that are not yet adaptive. State administration has an important role in supporting this transformation through adaptive regulations, incentives for industry, and human resource capacity improvement programs. To achieve success in implementing the Industrial Revolution 4.0, collaboration between government, industry, and academics is needed